The Relationship between Body Mass Index (BMI) and Total Cholesterol Levels in the Elderly in Warisa Village, Kampung Baru, Talawaan District, North Minahasa Regency - Gita Lara Br. Ginting, Tabitha; I. S. Wungouw, Herlina; Vanda Daturara Doda, Diana (Riviera Publishing, 2025)
Cholesterol is a fatty compound produced by various cells in the body. Increased levels of total cholesterol in the blood are the main cause of the burden of disease in developed and developing countries, namely as a risk factor for heart disease and stroke. Cholesterol levels are influenced by many factors, one of which is the body mass index (BMI). A person with a large BMI, will experience an increase in fat levels which can cause an imbalance in fat metabolism so that it can ultimately affect a person's body cholesterol levels. Therefore, this study aims to determine the relationship between BMI and total cholesterol levels in the elderly in Warisa Kamung Baru Village, Talawaan District, North Minahasa Regency. This type of research is descriptive analytical using a correlation research design with a cross sectional approach. The sampling technique is total sampling. The sample in this study is 50 elderly people in Warisa Kampung Baru Village. The instruments used are scales, microtoise, autocheck GCU meters, pen lancet, cholesterol strips, cotton alcohol and sterile gloves. The data was analyzed using the Spearman correlation test with a significance value of p> 0.05, then H0 was accepted and H1 was rejected. A total of 50 elderly people participated in this study with most having a normal BMI (44.0%), underweight (2.0%), overweight (18.0%), obese 1 (24.0%), obese 2 (12.0%). Most of the elderly who were respondents had good cholesterol (52%), high threshold cholesterol (30.0%) and high cholesterol (18.0%). This study concluded that there was no relationship between body mass index (BMI) and total cholesterol levels in the elderly in Warisa Kampung Baru Village, Talawaan District, North Minahasa Regency.